Cabazes de Nostalgia e Retóricas do Mar entre Malaca e Portugal - Pires, Ema Cláudia (2021)
Abstract: This text discusses relations between processes of objectification of the past, identity constructions and ways of living the present and imagining the future. Methodologically, the analysis stems from continuing ethnography in Portugal and Malaysia. Specifically, we discuss the relationship between experiences and expectations of/about a Creole group resident in Peninsular Malaysia that traces its origins to a genealogy of several centuries dating back to a Portuguese ancestry. Based on this analytical locus, it is shown how different categories of people, including expectations and everyday experiences, weave their lives intertwined in imaginary ideas of past and future. Resumo: Este texto discute relações entre processos de objectificação do passado, construções identi tárias e modos de viver o presente e imaginar o futuro. Metodologicamente, a análise decorre de etnografia continuada em Portugal e na Malásia. Em concreto, discutimos relações entre experiências e expectativas de/sobre um grupo crioulo residente na Malásia Peninsular que traça as suas origens numa genealogia de vários séculos que remontam a uma ancestralidade portuguesa. Partindo deste locus analítico, demonstrase como diferentes categorias de pessoas, entre experiências quotidianas e expectativas, tecem as suas vidas entrelaçadas em ideias imaginárias de passado e de futuro.